2021
DOI: 10.3389/fonc.2021.642328
|View full text |Cite
|
Sign up to set email alerts
|

WEE1 Inhibition in Combination With Targeted Agents and Standard Chemotherapy in Preclinical Models of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal cancer with high incidences of p53 mutations. AZD1775 (adavosertib, previously MK-1775) is a small molecule WEE1 inhibitor that abrogates the G2M checkpoint and can potentially synergize with DNA damaging therapies commonly used in PDAC treatment. The purpose of this study was to identify combination partners for AZD1775, including standard chemotherapy or targeted agents, in PDAC preclinical models. Low powered preliminary screens demonstrated that tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…To illustrate the biological function in the two subtypes of PDAC patients, we carried out the GSVA enrichment analysis, and the results found that, compared with the cluster A subtype, immune-related pathways, such as the T cell receptor signaling pathway and the B cell receptor signaling pathway, were significantly inhibited in the cluster B subtype, while other pathways related to PDAC progress, such as the cell cycle and the p53 signaling pathway, were significantly increased. It is well known that the cell cycle and the p53 signaling pathway play important roles in the development and progression of PDAC (25)(26)(27). The results of this study further suggest that m 6 A methylation regulators may play an important role in the pathologic progression of PDAC by regulating related signaling pathways.…”
Section: Discussionsupporting
confidence: 68%
“…To illustrate the biological function in the two subtypes of PDAC patients, we carried out the GSVA enrichment analysis, and the results found that, compared with the cluster A subtype, immune-related pathways, such as the T cell receptor signaling pathway and the B cell receptor signaling pathway, were significantly inhibited in the cluster B subtype, while other pathways related to PDAC progress, such as the cell cycle and the p53 signaling pathway, were significantly increased. It is well known that the cell cycle and the p53 signaling pathway play important roles in the development and progression of PDAC (25)(26)(27). The results of this study further suggest that m 6 A methylation regulators may play an important role in the pathologic progression of PDAC by regulating related signaling pathways.…”
Section: Discussionsupporting
confidence: 68%
“…Wee1, a kinase which phosphorylates and represses Cdk1 activity, has dual roles in regulating entry into mitosis and maintaining HR proficiency [ 184 ]. In preclinical work, Wee1 inhibition sensitizes HR-proficient pancreatic cancer to chemotherapy and radiation [ 185 , 186 , 187 ]. Furthermore, Wee1 inhibition reduced Cdk1 phosphorylation in patients and shows significant potential as a radio-sensitizing strategy in combination with gemcitabine for the treatment of patients with locally advanced pancreatic cancer [ 188 ].…”
Section: Inducing Hrdmentioning
confidence: 99%
“…The data used to illustrate and implement these approaches examined the effect of the combination of AZD1775 provided by AstraZeneca or purchased from MolPool (Hong Kong) with Navitoclax purchased from Active Biochem (“drug AB”) versus a placebo treatment (“vehicle”). A subset of data from a past experiment on 1 PDX line for triple‐negative breast cancer (TNBC012) is used to illustrate the different methods where 2 tumors were planted into the hind flanks of each mouse as described previously 2,15,16 . These tumors were repeatedly measured at unequally spaced days.…”
Section: Methodsmentioning
confidence: 99%